The impact of the transition to the green economy on the balance of the relationship between the economic growth and the environmental deterioration in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The transition to the green economy is the goal of all the developing and the developed countries because it contributes to achieving balance in the use of the economic resources in the processes of growth and economic development, and takes environmental considerations when striving to achieve high rates of growth and balanced economic development, especially in light of the current stage of reconstruction. The Syrian economy must be balanced and rationalized in the use of resources and achieve balanced development that takes into account the relationship between the economic growth and deterioration and the environmental imbalance. Based on that, this study came to analyze the impact of applying green initiatives on the Syrian economy in achieving a balance between the economic growth and the environmental deterioration. The research concluded that the application of the green economy policies and principles achieve a number of benefits, foremost of which is the opening of new areas for the economic growth in accordance with a positive relationship with the environment, the promotion of low-carbon activities, the creation of new job opportunities, and the opening of new sources of income.